CCAR‐1 is a negative regulator of the heat‐shock response in Caenorhabditis elegans. Issue 5 (12th July 2018) - Brunquell, Jessica; Raynes, Rachel; Bowers, Philip; Morris, Stephanie; Snyder, Alana; Lugano, Doreen; Deonarine, Andrew; Westerheide, Sandy D.
Abstract: Defects in protein quality control during aging are central to many human diseases, and strategies are needed to better understand mechanisms of controlling the quality of the proteome. The heat‐shock response (HSR) is a conserved survival mechanism mediated by the transcription factor HSF1 which functions to maintain proteostasis. In mammalian cells, HSF1 is regulated by a variety of factors including the prolongevity factor SIRT1. SIRT1 promotes the DNA‐bound state of HSF1 through deacetylation of the DNA‐binding domain of HSF1, thereby enhancing the HSR. SIRT1 is also regulated by various factors, including negative regulation by the cell‐cycle and apoptosis regulator CCAR2. CCAR2 negatively regulates the HSR, possibly through its inhibitory interaction with SIRT1. We were interested in studying conservation of the SIRT1/CCAR2 regulatory interaction in Caenorhabditis elegans, and in utilizing this model organism to observe the effects of modulating sirtuin activity on the HSR, longevity, and proteostasis. The HSR is highly conserved in C. elegans and is mediated by the HSF1 homolog, HSF‐1. We have uncovered that negative regulation of the HSR by CCAR2 is conserved in C. elegans and is mediated by the CCAR2 ortholog, CCAR‐1. This negative regulation requires the SIRT1 homolog SIR‐2.1. In addition, knockdown of CCAR‐1 via ccar‐1 RNAi works through SIR‐2.1 to enhance stress resistance, motility, longevity, and proteostasis. This work therefore highlights the benefits of enhancing sirtuin activity to promote the HSR at the level of the whole organism.